Analgesic interaction between ondansetron and acetaminophen after tonsillectomy in children: The Paratron randomized, controlled trial. (2nd September 2014) - Ramirez, L.; Cros, J.; Marin, B.; Boulogne, P.; Bergeron, A.; de Lafont, G.E.; Renon‐Carron, F.; de Vinzelles, M‐A.; Guigonis, V.; Nathan, N.; Beaulieu, P.
Abstract Background The mechanism of action of acetaminophen remains unclear. One hypothesis involves an interaction with the serotoninergic system. Antagonists to serotonin (5‐HT)3 receptors (setrons) have antiemetic properties. Therefore, co‐administration of acetaminophen and a setron could lead to a decrease or a loss of acetaminophen analgesic effects. The aim of this study was to demonstrate such an interaction. Methods P aratron is a prospective, randomized, controlled, double‐blind, parallel group trial. All children aged 2–7 years (n = 69) scheduled for a tonsillectomy ± adenoidectomy received intraoperative acetaminophen with ondansetron or droperidol. Pain scores [Children's Hospital of Eastern Ontario Pain Scale (CHEOPS)], morphine consumption and the incidence of post‐operative nausea and vomiting (PONV) were measured for 24 h following surgery. Results Pain scores were not different at all times between the groups but median morphine consumption (μg) in recovery was 322.5 [interquartile range (IQR) 0.0–500.0] and 0 (IQR 0‐0) in the ondansetron (n = 35) and droperidol (n = 34) groups, respectively (p = 0.004). The percentages of patients who received morphine titration were 57.1% and 20.6% in the ondansetron and droperidol groups, respectively (p = 0.008). No significant difference was found for PONV. Conclusions An interaction between acetaminophen and ondansetron is suggested, with children receiving three times more morphine during pain titration in the recovery room. More studies are necessary to evaluate whether this finding is clinically relevant enough to preclude the simultaneous perioperative administration of both drugs in the future.